Studi Komparatif Al-Qur'an Tarjamah Tafsiriyah M. Thalib dan Terjemah Kemenag terhadap Kata “Fitnah” pada Surat Al-Baqarah - Mukhammad Lutfi (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2023)
This study aims to examine the comparison of Al-Qur'an Tarjamah Tafsiriyah M. Thalib and Al-Qur’an Terjemah Kemenag in translating the word “fitnah” in QS. Al-Baqarah verses 102, 191, 193 and 217. This study uses a library research approach that utilizes the Al-Qur'an Tarjamah Tasiriyah M. Thalib and Al-Qur’an Terjemah Kemenag as the unit of analysis. The data in this study are analyzed comparatively by comparing the translations of the two by revealing the similarities and differences along with the author's criticism. The dominant translation of the word